Pemberdayaan ekonomi rumah tangga yang terdampak pandemi Covid-19 melalui usaha mikro dan kecil di Kelurahan Mustikajaya - Nirdukita Ratnawati; Tatik Mariyanti; Syofriza Syofyan; Debbie Aryani Tribudhi; Soeharjoto Soeharjoto (Yumary: Jurnal Pengabdian kepada Masyarakat, 2020)
Purpose: This activity aims to improve the economic condition by managing and obtaining funding sources and increasing marketing using technology. Community Method: Service is carried out using the guidance and mentoring method by providing material on Islamic financial institutions, culinary businesses, and the use of technology. Results: Results from this activity were that participants could increase their understanding of the material provided by an average of 93 percent, which could be used to motivate and increase sales turnover. This happened because participants have knowledge of Islamic financial institutions as managers and sources of funding, culinary efforts to increase diversification in the food business, and use of technology to improve marketing and administration. Conclusion: Community services implemented during the pandemic must follow health protocols, whether offline or online. This service’s result is not optimal because it could not interact directly in giving and receiving material. Post of community services, the community’s economy improved because it can increase partners’ insight in overcoming capital and marketing problems, so they are motivated to develop their business. Keywords: Empowerment, Home economics, Covid-19